Effect on Onset and Duration of Sensory and Motor Block with Single Bolus Dose of Intravenous Dexmedetomidine as an Adjuvant on Spinal Anesthesia with 0.5% Hyperbaric Bupivacaine in Lower Limb Surgery - Bhattarai, Rupak; Shah, Parasmani; Sharma, Prabin (Journal of Nobel Medical College, 2023)
Background: The hyperbaric bupivacaine is being widely used for spinal anesthesia in lower limb surgeries. Dexmedetomidine can be used intravenously as well as an intrathecal injection along with spinal anesthesia for surgery below the umbilicus. Materials and Methods: This was a prospective, randomized double blinded study, where 100 patients posted for elective lower limb surgery under spinal anesthesia were divided into two groups. Group A received 0.5% hyperbaric bupivacaine as spinal anesthesia along with intravenous infusion of 0.5 μg /kg/hour of dexmedetomidine over a period of ten minutes. Group B received 0.5% hyperbaric bupivacaine as spinal anesthesia along with intravenous normal saline over a period of ten minutes. Results: The onset of sensory block was 3.19 ± 0.31 minutes in group A whereas 4.5 ± 0.22 minutes in group B. The onset of motor block was 4.28 ± 1.02 minutes in group A whereas 7.12 ± 0.87 in group B. The onset and duration of sensory and motor block were statistically significant. Regarding duration of sensory block, group A had 186.5 ± 14.04 minutes whereas group B had 148.2 ± 11.31 minutes with p value <0.001. The duration of motor block was 142 ± 11.42 minutes in group A whereas 122.4 ± 8.28 minutes in group B with p value <0.001. The duration of postoperative analgesia was prolonged in group A when compared with group B. Conclusion: Dexmedetomidine used as a single intravenous injection along with spinal anesthesia with 0.5% bupivacaine tends to shortens the onset of both sensory and motor blocks and increases the duration of sensory and motor blocks. It also prolongs the duration of analgesia with minimal or no changes in hemodynamic parameters.